Predictors of external whistleblowing intentions in Sime Darby Berhad / Mohd Rozaimy Ridzuan - Ridzuan, Mohd Rozaimy (2015)
Scholars' interest pertaining to whistleblowing study is becoming increasingly prevalent due to the debacle of giant multinational companies in the United States and the emergence of legal protections for whistleblowers in several countries. In Malaysia, there are several giant companies involved in corporate wrongdoings and one of them is Sime Darby Berhad. Since whistleblowing is a useful means to reduce the corporate wrongdoings, hence, this study aims to examine factors that influence external whistleblowing intentions among Sime Darby staffs. External whistleblowing channel is examined in the study as the Whistleblower Protection Act (WBPA) 2010 only protect the whisletblower who reports wrongful act to the enforcement agencies (external parties). There are three main predictors in this study that are predicted to influence external whistleblowing intentions, which are organizational, individual and situational predictors. The awareness of Malaysian Whistleblower Protection Act 2010 is predicted to moderate the relationship between variables. This quantitative study focused on Sirne Darby staffs by using the hypotheses testing and utilizing questionnaires as a means to collect the data from the respondents. The study found that the benevolence (organizational predictor), organizational commitment (individual predictor) and the seriousness of wrongdoing (situational predictor) significantly influenced external whistleblowing intentions among staff in Sime Darby Berhad. This empirical study is vital as it is able to add on the information to the existing body of knowledge on whistleblowing matters in Malaysia. The findings of the study also will help the management of Sime Darby to delineate a sound whistleblowing policy so that it will encourage more staff to blow the whistle on wrongdoings to the enforcement agencies.